Application Of Media Literacy Elements In Students In The Independent Learning Process (Texas Journal of Multidisciplinary Studies, 2021)
This article covers the matters related to designing self-education of masters of technical higher educational institutions. Here will be listed variety types of independent work, as well as components of pedagogically designing the process of master self-education. Apparently, the independent work of the master is one of the main components of self-education.